Preventing Audit Quality Risks in Independent Audit: A Road Map in the Light of Theoretical Approaches - KIZILTAN IŞIK, Burçak; VURAL, Aslı (International Journal of Contemporary Economics and Administrative Sciences, 2025)
An independent audit is a critical system for ensuring that a company’s financial statements are accurate and reliable. However, the quality risks inherent in the detail of the audit make it difficult to deploy this function effectively. These risks, which are composed of variables such as accounting standards, auditing techniques, management strategies and technological developments, need to be controlled. The purpose of this study is to provide theoretical and practical ways to prevent quality risks in auditing and to establish an effective quality management system. In this study management structure, technological infrastructure, professional standards, external service providers and factors; have been examined the causes and solutions of these risks were examined using theoretical frameworks such as the systems approach, organization theory, source and emission theory. The study continues to emphasize that the governance structure and the adoption of corporate governance policies are crucial to enhance supervision. It was stated that audits should ensure continuous compliance, perform a risk-focused practice, and establish a dynamic quality management system. The study concluded that audit credibility can be enhanced by working in harmony with technical and organizational elements. Effective management, adherence to ethical values, technological integration and compliance protection are the most prominent factors in sustainably maintaining the audit. Audit intervals should be supported through continuous training and technology compliance programs, and cooperation and information sharing in audit networks should be improved. This study provides a summary guide to improving the efficiency of audit funding and summarizing quality risks.